2001
DOI: 10.1128/aac.45.8.2287-2298.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Class A β-Lactamase Sed-1 from Citrobacter sedlakii : Genetic Diversity of β-Lactamases within the Citrobacter Genus

Abstract: Citrobacter sedlakii 2596, a clinical strain resistant to aminopenicillins, carboxypenicillins, and early cephalosporins such as cephalothin, but remaining susceptible to acylureidopenicillins, carbapenems, and later cephalosporins such as cefotaxime, was isolated from the bile of a patient treated with ␤-lactam and quinolone antibiotics. The isolate produced an inducible class A ␤-lactamase of pI 8.6, named Sed-1, which was purified. Characterized by a molecular mass of 30 kDa, Sed-1 preferentially hydrolyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 60 publications
2
51
0
Order By: Relevance
“…The ␤-lactam susceptibility pattern of E. hermannii was similar to that of K. pneumoniae, K. oxytoca, Citrobacter koseri, and Serratia fonticola (16,19,21). Susceptibility to cefuroxime distinguished E. hermannii from Rahnella aquatilis, Citrobacter sedlakii, and Proteus vulgaris (2,20,21). These results suggested that E. hermannii produces a class 2a ␤-lactamase (5).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…The ␤-lactam susceptibility pattern of E. hermannii was similar to that of K. pneumoniae, K. oxytoca, Citrobacter koseri, and Serratia fonticola (16,19,21). Susceptibility to cefuroxime distinguished E. hermannii from Rahnella aquatilis, Citrobacter sedlakii, and Proteus vulgaris (2,20,21). These results suggested that E. hermannii produces a class 2a ␤-lactamase (5).…”
supporting
confidence: 49%
“…All the strains were susceptible to cephalothin, cefuroxime, cefoxitin (Table 2), and broad-spectrum cephalosporins (MICs, Ͻ0.06 g/ml), aztreonam (MICs, Ͻ0.06 g/ ml), and imipenem (MICs, 0.06 to 0.12 g/ml). The ␤-lactam susceptibility pattern of E. hermannii was similar to that of K. pneumoniae, K. oxytoca, Citrobacter koseri, and Serratia fonticola (16,19,21). Susceptibility to cefuroxime distinguished E. hermannii from Rahnella aquatilis, Citrobacter sedlakii, and Proteus vulgaris (2,20,21).…”
mentioning
confidence: 74%
“…Klebsiella pneumoniae, Klebsiella oxytoca, Proteus mirabilis, and Salmonella spp. (31) lack a chromosomal bla AmpC gene, as do Citrobacter amalonaticus (328), Citrobacter farmeri, Citrobacter gillenii (224), Citrobacter koseri (formerly Citrobacter diversus and Levinea malonatica), Citrobacter rodentium, Citrobacter sedlakii (252), Edwardsiella hoshinae, Edwardsiella ictaluri (312), Kluyvera ascorbata (138,305), Kluyvera cryocrescens (72), Plesiomonas shigelloides (9), Proteus penneri (175), Proteus vulgaris (60), Rahnella aquatilis (30,308), Yersinia pestis, and Yersinia pseudotuberculosis (313) as well as, probably, Escherichia hermannii (91), Francisella tularensis (27), Shewanella algae (123), and Stenotrophomonas maltophilia (111). However, since bla AmpC genes occur on transmissible plasmids, the clinical microbiologist needs to consider this resistance mechanism whatever the identification of an organism.…”
Section: Distributionmentioning
confidence: 99%
“…1). Indeed, some class A ␤-lactamases closely related to K. ascorbata enzymes are regulated by an ampR gene: cumR (Proteus vulgaris) (5), sedR (C. sedlakii), (19) and fonR (S. fonticola) (C. Humeniuk, unpublished data).…”
Section: Bacterial Strainsmentioning
confidence: 99%